Making Ensemble Possible: How special groups organize for collaborative creativity in conditions of spatial variability and distance - Shannon O'Donnell (Copenhagen Business School (CBS), 2013)
The enormous challenges and opportunities impacting the world community today increasingly require people to practice collaborative innovation effectively both in person and across geographic boundaries. Simultaneously, advances in technology such as social networking tools, digital 3-D representations, virtual worlds, and open source practices are inspiring generations of users to develop new kinds of adaptive collaborative networks and capabilities. But when people work across organizational and geographic boundaries, new challenges arise that make it difficult for groups to achieve the levels of excellence they are capable of achieving together in close proximity. Practitioners need help determining how best to perform collaborative creativity given unique and dynamic work conditions. Meanwhile, as new forms of creative group work emerge at an accelerating pace, researchers struggle to keep up with and develop nuanced understanding of the variations in collaborative processes we increasingly see performed. With this PhD research, I aim to increase our understanding of a particular, specialized form of collaborative creativity called “ensembling.” I investigate this phenomenon by studying it in diverse—including “stretched”—conditions. By stretched, I mean that, literally, groups are stretched apart in space as membership size and spatial distance between members increase and work configurations vary. The groups I study are those both capable of achieving and driven to achieve a peak-performance state of ensemble, and do so via the enactment of an interdependent set of methods that call ensemble into being, a process I call ensembling. In their ideal form, these work methods support the emergence of ensemble and result in the creation of aesthetically coherent and novel outcomes that are particularly responsive to the contexts in which they are made. To investigate the phenomenon of ensemble, I first develop a construct of ensemble based on informant descriptions, and use theory and data to develop a detailed description of how ensembling is performed in natural conditions (i.e., in close physical proximity). Then I look at an extreme example in which a set of expert groups' ability to ensemble was put under stress by an unprecedented work task. In 2009, multiple string quartets (many considered world class) organized to perform a new musical composition. The composition challenged four quartets at a time to perform as an integrated ensemble while sitting apart, in various configurations, and at spatial distances of up to 70 feet. To help them address the difficulties produced by increased membership and distance, the musicians integrated a simple coordinating technology into their process. To learn how participants made ensemble possible given these new conditions, I engaged multiple qualitative methods for generating data and multiple perspectives for interpretation. I first considered their process as an iterative approach to exploring strategies for addressing constraints, in order to show how the methods of ensembling interacted with conditions of increased group size, increased spatial distance and configurational variability, and to elicit their evolving beliefs about what methods made ensemble more likely to occur given these conditions. Then I performed an alternative interpretation, disrupting this logic and exploring the ways in which participants used methods of ensembling—particularly openness to uncertainty and reconceiving—to create unanticipated potentialities for ensemble to emerge despite constraints. I show how they worked with a coordinating technology called a “click-track” in important new ways that went beyond “merely” achieving synchronous coordination to increasing their autonomy, relatedness, and ability to demonstrate artistic virtuosity, enabling them to engage equally in leadership and participation and to play. Finally, performing a comparative analysis across sub-units of the case, including examples of breakdown in the process, I generated additional insights into what conditions, beliefs, methods and behaviors enable or inhibit processes of ensembling. Integrating learning from analysis and interpretation, I propose a new range of conditions in which ensembling is possible, and a revised and expanded description of the methods by which groups ensemble. Conditions can expand to include larger groups with limited-tenure consisting of enduring-tenure sub-groups, multiple task interdependencies at group and sub-group levels, balanced tenure at sub-group level, a balance between proximity and distance, opportunities to work with and without technological mediation, and self-determined configuration variability. I show that the emergence of ensemble depends on, for instance, a shared purpose to ensemble, and methods such as a “struggle” phase, episodes of close physical proximity, collective leadership, “dueting” in different configurations, reconceiving constraints, living with the paradox of one-and-four, opening the process to uncertainty and to the emergence of consent, and subliminal technology engagement. Ultimately, these groups demonstrated an increasing ability to adapt to new conditions faster and more creatively, making new configurations possible, and suggesting ways in which ensemble might be performed in other kinds of group settings. I summarize findings in the form of a “framework of ensembling” that is meant to serve as a tool to further enrich our yet nascent understanding of this complex phenomenon and to aid in the exploration of ensembling in contexts outside the usual places we expect it to occur.
hdl:10398/8653
Keywords: 650